Post Traumatic Buccal Fat Pad Injury in a Child: A missed entity in ER - Singhal, Maneesh (Oman Med J, 2010)
Maxillofacial injuries in the paediatric age group is common and traumatic herniation of buccal fat pad represents one of the few sequel to facial injuries which can easily be missed during primary or secondary survey in the emergency department, especially in young patients. The uncommon occurrence and thus lack of knowledge, often alarms the parents and/or attending physian alike with the presence of a tumor like lesion within the oral cavity in the post-traumatic period. The following case report describes one such incidence of traumatic extrusion of the buccal fat pad into the oral cavity while addressing the need to reinforce the practice of thorough clinical examination before managing any patient.